Engagement's Possibilities and Limits As a Socioeconomic Rights Remedy - Brian Ray (Washington University Global Studies Law Review, 2010)
This Article first analyzes the Court‘s three engagement decisions. It then divides engagement into two different categories-litigation engagement and political engagement-and offers suggestions for transforming the process into a more effective remedy in each category.
Keywords: Housing -- South Africa; Civil rights -- South Africa; Municipal corporations; Eviction; Mediation; Administrative arbitration